Florid cemento-osseous dysplasia in a young Chinese man. Case report - Ong, S.T.; Siar, C.H. (1997)
Florid cemento-osseous dysplasia refers to a group I of fibro-osseous lesions which are exuberant, multi-quadrant and arise from the tooth-bearing area of the jaws. It is classically described as a condition occurring almost exclusively in middle-aged black women. A case of florid cemento-osseous dysplasia occurring in a young Chinese male is reported which was rare in regard to race and sex. This 20 year old Chinese man presented with huge symmetrical bony lesions in all four quadrants of the jaws. Clinical presentation, radiological findings and histological features of the excised specimens are described treatment of the lesions was unusual. Curettage was first done with minimal benefit and it was followed by mandibular recontouring to improve facial appearance. The outcome of these procedures will be discussed.